All-spinel oxide Josephson junctions for high-efficiency spin filtering - Mesoraca, S; Knudde, S; Leitao, D C; Cardoso, S; Blamire, M G (Journal of physics. Condensed matter, 2018)
Obtaining high efficiency spin filtering at room temperature using spinel ferromagnetic tunnel barriers has been hampered by the formation of antiphase boundaries due to their difference in lattice parameters between barrier and electrodes. In this work we demonstrate the use of LiTi2O4 thin films as electrodes in an all-spinel oxide CoFe2O4-based spin filter devices. These structures show nearly perfect epitaxy maintained throughout the structure and so minimise the potential for APBs formation. The LiTi2O4 in these devices is superconducting and so measurements at low temperature have been used to explore details of the tunnelling and Josephson junction behaviour.